Effect of Resident Physician Education Regarding Selective Chemoprophylaxis for the Prevention of Early Onset Group B Streptococcal Sepsis: An Outcome Study. Issue 5 (1994) - Greenspoon, Jeffrey S.; Rosen, Doron J. D.; Sumen, Anita P.
Abstract : Objective: The aim of this study was to evaluate the effect of a voluntary protocol for selective intrapartum chemoprophylaxis on the incidence of early onset group B streptococcal sepsis (GBS EOS). Methods: Cases of GBS EOS were defined as a positive GBS culture from a normally sterile fluid obtained during the first 7 days of life. All cases of GBS EOS at an urban, university-affiliated community hospital were reviewed during 2 time periods. The 2-year period before instituting a resident education program to promote selective chemoprophylaxis (1988–89) was retrospectively reviewed; the 2-year period after the education program was introduced (1990–91) was prospectively recorded. The outcome measure was the incidence of GBS EOS. Results: The rate of GBS EOS was 7/14, 335 deliveries (0.05%) before and 9/13, 999 (0.064%) after the introduction of the education program (observed difference between proportions 0.016%, 95% confidence interval [CI] for the difference between the proportions –0.071% to 0.04%, P = not significant [NS]). The rate of GBS EOS in preterm infants was 5/1, 331 (0.376%) before and 3/1, 297 (0.23%) afterward (observed difference between proportions 0.14%, 95% CI –0.28% to 0.56%, P = NS). The incidence of GBS EOS did not decrease during the latter period due to failure of antepartum cultures to predict intrapartum GBS colonization (2 cases); non-compliance with voluntary recommendations to administer chemoprophylaxis (2 cases); failure of chemoprophylaxis or therapy for intraamniotic infection to prevent neonatal infection (3 cases); and occurrence of GBS EOS in infants without risk factors (2 cases). Conclusions: An education program for resident physicians regarding chemoprophylaxis for GBS EOS did not significantly reduce the absolute incidence of disease. Alternative strategies are needed that redress the causes of failure inherent in the current guidelines. Some cases of GBS EOS are not preventable because the parturient does not have risk factors that indicate chemoprophylaxis.